Simufilam suppresses overactive mTOR and restores its sensitivity to insulin in Alzheimer’s disease patient lymphocytes - Wang, Hoau-Yan; Pei, Zhe; Lee, Kuo-Chieh; Nikolov, Boris; Doehner, Tamara; Puente, John; Friedmann, Nadav; Burns, Lindsay H. (Frontiers in Aging, 2023)
Introduction: Implicated in both aging and Alzheimer’s disease (AD), mammalian target of rapamycin (mTOR) is overactive in AD brain and lymphocytes. Stimulated by growth factors such as insulin, mTOR monitors cell health and nutrient needs. A small molecule oral drug candidate for AD, simufilam targets an altered conformation of the scaffolding protein filamin A (FLNA) found in AD brain and lymphocytes that induces aberrant FLNA interactions leading to AD neuropathology. Simufilam restores FLNA’s normal shape to disrupt its AD-associated protein interactions. Methods: We measured mTOR and its response to insulin in lymphocytes of AD patients before and after oral simufilam compared to healthy control lymphocytes. Results: mTOR was overactive and its response to insulin reduced in lymphocytes from AD versus healthy control subjects, illustrating another aspect of insulin resistance in AD. After oral simufilam, lymphocytes showed normalized basal mTOR activity and improved insulin-evoked mTOR activation in mTOR complex 1, complex 2, and upstream and downstream signaling components (Akt, p70S6K and phosphorylated Rictor). Suggesting mechanism, we showed that FLNA interacts with the insulin receptor until dissociation by insulin, but this linkage was elevated and its dissociation impaired in AD lymphocytes. Simufilam improved the insulin-mediated dissociation. Additionally, FLNA’s interaction with Phosphatase and Tensin Homolog deleted on Chromosome 10 (PTEN), a negative regulator of mTOR, was reduced in AD lymphocytes and improved by simufilam. Discussion: Reducing mTOR’s basal overactivity and its resistance to insulin represents another mechanism of simufilam to counteract aging and AD pathology. Simufilam is currently in Phase 3 clinical trials for AD dementia.